Nonhydrolytic Route to Boron‐Doped TiO2 Nanocrystals. Issue 3 (26th November 2012) - Xu, Hua; Picca, Rosaria Anna; De Marco, Luisa; Carlucci, Claudia; Scrascia, Angela; Papadia, Paride; Scremin, Barbara Federica; Carlino, Elvio; Giannini, Cinzia; Malitesta, Cosimino; Mazzeo, Marco; Gigli, Giuseppe; et al.
Abstract: A simple synthesis was applied and tested for the preparation of boron‐doped titanium dioxide [TiO2 (B)] nanocrystals using titanium tetraisopropoxide (TTIP) together with boric acid (H3 BO3 ) and benzyl alcohol as reaction solvent. Changes in the TTIP/H3 BO3 molar ratio allowed a scalable synthetic protocol with a significant B‐dopant control. In particular, this approach does not need surfactants or a final calcination step. X‐ray diffractometry (XRD), low‐ and high‐resolution transmission electron microscopy (TEM and HRTEM), and micro Raman spectroscopy revealed that the TiO2 nanocrystals produced have diameters up to about 10 nm and are mainly of the anatase phase but that a brookite phase was progressively formed with increased dopant level. The amount of boron was measured by inductively coupled plasma atomic emission spectroscopy (ICP‐AES), and the presence of boron inside the crystals was determined by 11 B cross‐polarized magic‐angle spinning nuclear magnetic resonance ( 11 B CP‐MAS NMR) spectroscopy. X‐ray photoelectron spectroscopy (XPS) revealed the presence of boron on the nanocrystal surfaces, confirming the trend in the dopant concentration already observed with ICP‐AES elemental analysis. Microphotoluminescence studies indicated the formation of three different typical luminescent defect states in correlation with the amount of added boron in the titania. UV/Vis absorption spectra showed a boron‐dependent redshift of the absorption edge. Abstract : A surfactant‐free synthesis of highly crystalline boron‐doped TiO2 anatase nanocrystals and their properties are reported. The final product may be obtained in a single step of a few hours only, at a moderate temperature without calcination. The band gap of the crystals varies with the amount of dopant.